The relationship between family support and stress in the elderly with type 2 diabetes mellitus in the work area of the pidie health center, pidie regency - Mu’alim, Azhar; Ismuntania; Mufida, Nurlela; Iqbal, Muhammad; Rakhman, Fakhryan (Trigin Institute, 2023)
The high incidence of diabetes mellitus cannot be separated from the problem of low family support, especially for the elderly. The aim of the research was to determine the relationship between family support and the incidence of stress in elderly people with type 2 diabetes mellitus. The method used analytical research with a cross-sectional design on 65 elderly people in the Pidie Health Center Working Area. Implementation time starts from 14-20 July 2023. Sample collection uses purposive sampling technique. The data analysis used was the Chi-Square Test. The results of the research show that there is a relationship between family support and the incidence of stress in elderly people with type 2 diabetes mellitus in the work area of the Pidie Health Center (p value 0.002) α = 0.005). The conclusion is that the majority of elderly people with type 2 diabetes mellitus do not receive family support with mild stress, namely 28 elderly people (43.1%), the majority of elderly people with type 2 diabetes mellitus experience severe stress with less supportive family support, namely 9 elderly people ( 13.8%), there is a significant relationship between family support and the incidence of stress in elderly people suffering from type 2 diabetes mellitus in the work area of the Pidie Health Center, Pidie Regency in 2023, with the Chi-Square statistical test obtaining a P-value of 0.002 < 0.05. The suggestion is that elderly families can provide good family support so as not to cause stressful events and can prevent stress in elderly people with type 2 diabetes mellitus